Enabling Quality of Service Provision in Omni‐Path Switches. Issue 6 (9th February 2021) - Cano‐Cano, Javier; Andújar, Francisco J.; Alfaro‐Cortés, Francisco J.; Sánchez, José L.
Abstract: The increasing demand of high‐performance services has motivated the need of the 1 exaflop supercomputing performance. In systems providing such computing capacity, the interconnection network is likely the cornerstone due to the fact that it may become the bottleneck of the system degrading the performance of the entire system. In order to increase the network performance, several improvements have been introduced such as new architectures. Intel © Omni‐Path architecture (OPA) is an example of the constant development of high‐performance interconnection networks, which has not been largely studied because it is a recent technology and the lack of public available information. Another important aspect of all interconnect network technologies is the Quality of Service (QoS) support to applications. In this article, we present an OPA simulation model and some implementation details as well as our simulation tool OPASim. We also review the QoS mechanisms provided by the OPA architecture and present the table‐based output scheduling algorithm simple bandwidth table.